Improving lifestyle obesity treatment during the COVID‐19 pandemic and beyond: New challenges for weight management - Ann E. Caldwell; Elizabeth A. Thomas; Corey Rynders; Brooke Dorsey Holliman; Cathryn Perreira; Danielle M. Ostendorf; Victoria A. Catenacci (Wiley, 2022)
Abstract Objective The COVID‐19 pandemic has resulted in significant changes to daily life and many health‐related behaviors. The objective of this study was to examine how the stay‐at‐home/safer‐at‐home mandates issued in Colorado (March 2020-May 2020) impacted lifestyle behaviors and mental health among individuals with overweight or obesity participating in two separate behavioral weight loss trials (n = 82). Methods Questionnaires were used to collect qualitative and quantitative data on challenges to weight loss presented by the COVID‐19 pandemic, including changes in dietary intake, physical activity, sedentary behavior, and mental health during the stay‐at‐home/safer‐at‐home mandates. Results Using a convergent mixed method approach integrating qualitative and quantitative data, the greatest challenge experienced by participants was increased stress and anxiety, which led to more unhealthy behaviors. The majority perceived it to be harder to adhere to the prescribed diet (81%) and recommended physical activity (68%); however, self‐reported exercise on weekdays increased significantly and 92% of participants lost weight or maintained weight within ±1% 5-6 weeks following the stay‐at‐home mandate. Conclusion Study results suggest that obesity treatment programs should consider and attempt to address the burden of stress and anxiety stemming from the COVID‐19 pandemic and other sources due to the negative effects they can have on weight management and associated behaviors.